PENAKSIR RASIO YANG EFISIEN UNTUK VARIANSI POPULASI PADA SAMPLING ACAK SEDERHANA MENGGUNAKAN FRAKSI PENGAMBILAN SAMPEL - Rio Permadi; Bustami '; Haposan Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The estimators studied here are three ratio estimators for population variance in simple random sampling without replacement using sampling fraction. This study is a review of article written by Tailor and Sharma [Statistics in Transition-new series 13 (2012): 37-46]. All estimators are biased, then their mean square error (MSE) of the studied estimators are compared to obtain the most efficient estimator. An example is given to explain the studied problem.